2015
DOI: 10.1093/cid/civ679
|View full text |Cite
|
Sign up to set email alerts
|

PTX3-Based Genetic Testing for Risk of Aspergillosis After Lung Transplant: Table 1.

Abstract: Potential conflicts of interest. A. M. has been a consultant to Sigma Tau Pharmaceuticals (Pomezia, Italy) and a board member of the Istituto di Ricerche in Biomedicina (Bellinzona, Switzerland) and Efranat Ltd (Rehovot, Israel). A. M. has

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 8 publications
3
38
0
Order By: Relevance
“…In the light of our results on PTX3, genetically-targeted antifungal prophylaxis would be particularly useful in patients with intensive chemotherapy for AL in which universal prophylaxis is not always made, although IA remains more frequent than in SOT patients (11,12).…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…In the light of our results on PTX3, genetically-targeted antifungal prophylaxis would be particularly useful in patients with intensive chemotherapy for AL in which universal prophylaxis is not always made, although IA remains more frequent than in SOT patients (11,12).…”
mentioning
confidence: 91%
“…Previous studies showed robust associations between these SNPs and IMIs among both HSCT (9, 10) and SOT recipients (11,12). The strength of theses associations, together with relative high allele frequency of the SNPs and replication among different at-risk population have made PTX3 SNPs the most reliable marker of IMIs in these populations.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Interestingly, PTX3 polymorphisms were recently associated with susceptibility to A. fumigatus infection in two cohorts of patients undergoing bone marrow transplantation [37]. The association between genetic polymorphisms and susceptibility to mold infections was recently independently confirmed in 1101 patients of the Swiss Organ Transplantation Cohort [38] and in a small cohort of lung transplantation patients [39].…”
Section: Protective Role Of Ptx3 In Pathogen Defencementioning
confidence: 94%
“…29 The same haplotype was associated with IA in 2 cohorts of solid organ transplant recipients. 37,38 PTX3 encodes long pentraxin 3, a soluble PRR that detects galactomannan from the fungi. PTX3 induces many immune processes such as pathogen opsonization, phagocytosis, complement activation, as well as clearance of apoptotic cells.…”
Section: Infectious Complications and Risk Assessment Of Hsct Recipientsmentioning
confidence: 99%